(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article highlights the importance of “Protection of the children by the parents especially, the children infected and affected with HIV/AIDS, protection against the stigma. Parents exhibit an enormous amount of patience in dealing with children and cope with the tantrums. Perseverance is followed by patience in helping them pursue them to do their daily chores and take medication regularly.